“Our old enemy the commodity”: Image, Narration, Spectacular Time - Daniel Barrow (Janeway JS, 2019)
Guy Debord and the Situationist International's analysis of late capitalist temporality remains an under-examined area of their work. Time as a 'form of appearance' - Marx's description of the commodity - replaces the reality of a time that cannot develop quantitatively. This article argues that this far-reaching analysis, which has been controversial in art theory and literary studies, sheds valuable light on theories of narrative time and subjectivity in late capitalist culture.